تقييم الاتصال الإداري (الإنصات الفعال) للاعبي ومدربي كرة اليد المشاركين في الدوري العراقي الممتاز 2018-2019 - عبدالسادة، غسان محمد; أحمد، محمد جاسم; كاظم، قاسم حسن (جامعة بابل - كلية التربية الرياضية, 2021)
حتى يتمكن الباحثون من تحقيق أهداف البحث في التعرف على مستوى الإنصات الفعال لدى كل من مدربي ولاعبي كرة اليد المشاركين في دوري العراق الممتاز للموسم. (2018-2019) ومعرفة الفروق بين المستويات التي هم عليها في هذه المهارة (الإنصات الفعال) كان ولابد أن الإجراءات المعنية بمنع البحث والذي سمي بالوصفي بأسلوب المسح والمعيار، كذلك تحديد مجتمع البحث وعيناته إذ أجريت هذه الدراسة على جميع لاعبي ومدربي فرق كرة اليد المشاركة في الدوري الممتاز. وبعد استعمال المقياس المخصص لقياس مهارة الإنصات الفعال - تم بناءه من قبل الباحث غسان محمد عبد السادة - تم الحصول على الاستنتاجات الآتية: 1- أن توزيع عينتي البحث من المدربين واللاعبين جاء اعتداليا في مهارة الإنصات الفعال مما يساعد في وضع المستويات المعيارية لها لأغراض التقييم في هذه المهارة. 2- حققت كل من عينتي البحث من المدربين واللاعبين مستوى عاما عاليا جدا في مهارة الإنصات الفعال وأن الأولوية للاعبين. The research aims to identify the effective listening level of each of the handball coaches and players participating in the Iraq Premier League for the season 2018-2019 ,and identify the differences between the levels at which they are in this skill (active listening). The descriptive approach of in the method of surveying and the standard was used to conduct the research as well as defining the research community and its samples. This study was conducted on all players and coaches of handball teams Participating in the Premier League. After using the scale designed to measure the skill of effective listening - which was built by the researcher Ghassan Muhammad Abd al-Sada - the following conclusions were obtained: 1.The distribution of the two research samples from coaches and players was moderate in the skill of active listening, which helps in setting standard levels for them for the purposes of evaluation in this skill. 2.Each of the two research samples of coaches and players achieved a very high level in the skill of effective listening, and the priority is for the players.
Keywords: الإدارة الرياضية -- الاتصالات الإدارية -- الإنصات الفعال -- الألعاب الرياضية